Structure-Profit Relationship at the Line of Business and Industry Level - Ravenscraft, David J. (The Review of Economics and Statistics, 1983)
A LTHOUGH much research has been done IA-t on the relationships between industrial structure and performance, important puzzles persist. Specifically, it remains unclear whether profits rise with industry concentration when other structural variables, such as market share, are appropriately held constant. Also, what economic phenomena underlie the observed positive profit-market share associations'? This paper seeks to clarify these relationships. Until recently, data limitations have restricted cross-sectional structure-performance analyses to either industry level variables or firm level variables which aggregate quite different activities within a single corporate financial statement.' These limitations are overcome by the Federal Trade Commission's Line of Business survey, which compiles financial statistics disaggregated to the of business (LB) level. A line of refers to a firm's operations in one of 261 manufacturing and 14 nonmanufacturing categories defined by the FTC. The number of LBs per company ranges from I to 47, with an average of 8 lines per company. For each LB, information on pretax profit, advertising, research and development, assets, market share, diversification and vertical integration is reported. When combined with census and input-output data, the FTC line of data allow the estimation of a structure-performance equation of unprecedented richness. A primary emphasis is placed on the theoretical and empirical differences between variables measured at the LB and industry level. To accomplish this task and to relate this paper to the previous literature, regressions are performed at both the LB and industry level.